(untitled) (EAAE Annual Conference Proceedings, 2023)
Moderated by Jan Kristek, Dean of the Faculty of Architecture at Brno University of Technology (since 2018), where he runs a design studio together with Jaroslav Sedlák. The panel was opened by a lecture by landscape architect Eric Luiten, defending his position that today’s multi-dimensional, comprehensive spatial programs and projects require explicit disciplinary experience, input and responsibilities. Along with this, he argues that the training of spatial designers should be focused on the transfer of knowledge, repertoire, skills and behaviour that can be recognised as specific professional expertise. There is no multidisciplinarity without monodisciplinary representation.